Cauca Sinfónico. Composiciones y Arreglos de Repertorio Caucano para Orquesta, Banda Sinfónica y Grupos de Cámara - Campo Gómez., Jorge Yeison (2025)
The artistic proposal presented here primarily consists of the creation of a Suite Caucana for symphony orchestra, composed of two contrasting movements. This work will incorporate characteristic rhythms from the department, such as bambuco and pasillo. Through this composition, the aim is to convey ethnic diversity by creating a sonic landscape that allows the listener to imagine the region’s population, biodiversity, and the striking contrasts of its scenery, as expressed through sectional changes. Additionally, the proposal includes the composition of a bambuco for solo chirimía caucana flute and piano—an effort to highlight the significance of this traditional instrument and its melodic leadership within the folk music context, integrating it with Western harmonic instruments. This approach seeks to emphasize traditional musical expressions through creative proposals that contribute to the preservation and safeguarding of traditional music while demonstrating its versatility within academic settings. Furthermore, the proposal includes the composition of a pasillo for solo trumpet and symphonic band, aimed at enriching the Colombian repertoire for developing musicians. This piece will create artistic spaces that allow performers to explore and experience the sounds of national folklore more deeply, serving as a strategy for preserving traditional music. Finally, the artistic project will conclude with a symphonic band arrangement of Los Arrayanes by composer Saúl Mera, set to a pasillo rhythm. This aspect of the proposal seeks to bring visibility to the works of local composers, facilitating their dissemination by incorporating them into academic formats. The initiative underscores the importance of strengthening the Colombian and Caucano repertoire within the symphonic band movement, which holds a strong cultural presence in the region